Centrality metrics for complex network analysis emerging research and opportunities - Meghanathan, Natarajan, 1977- (IGI Global, 2018)
"This book explores node and edge centrality metrics and real-world network graphs, computationally-light vs. computationally-heavy centrality metrics, centrality-based connected dominating sets for complex network graphs, assortativity analysis based on centrality metrics, time-dependent variation of the node centrality metrics during the evolution of a scale-free network, curriculum network graph analysis, and eigenvector centrality-based approach to detect graph isomorphism"--